2007
DOI: 10.1161/atvbaha.107.152272
|View full text |Cite
|
Sign up to set email alerts
|

Small Concentrations of oxLDL Induce Capillary Tube Formation From Endothelial Cells via LOX-1–Dependent Redox-Sensitive Pathway

Abstract: Objective-Vascular endothelial growth factor (VEGF), a key angiogenic growth factor, stimulates angiogenesis. Low levels of reactive oxygen species (ROS) function as signaling molecules for angiogenesis. We postulated that low concentrations of oxLDL might induce low levels of ROS and initiate angiogenesis. Methods and Results-An in vitro model of tube formation from human coronary artery endothelial cells (HCAECs) was used.oxLDL (0.1, 1, 2, 5 g/mL) induced VEGF expression and enhanced tube formation. oxLDL-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 45 publications
9
117
1
Order By: Relevance
“…Our studies, however, showed that oxLDL may have a positive effect on the formation of endothelial networks in a 3D in vitro model of angiogenesis (3,18). Consistent with these findings, a similar effect was shown in a 2D system (19). Most recently, it was shown that oxLDL also has a pro-angiogenic effect in vivo (20,21), possibly in a macrophage-dependent way (20).…”
Section: Lipid Extraction and Lc-ms/ms Analysis Of Oxysterolssupporting
confidence: 88%
“…Our studies, however, showed that oxLDL may have a positive effect on the formation of endothelial networks in a 3D in vitro model of angiogenesis (3,18). Consistent with these findings, a similar effect was shown in a 2D system (19). Most recently, it was shown that oxLDL also has a pro-angiogenic effect in vivo (20,21), possibly in a macrophage-dependent way (20).…”
Section: Lipid Extraction and Lc-ms/ms Analysis Of Oxysterolssupporting
confidence: 88%
“…Cell death ensues (Mehta et al, 2006;Chen et al, 2007). The amount of ROS determines beneficial or detrimental effects, either for endothelial cell survival or apoptosis (Dandapat et al, 2007). The same could hold true for the preovulatory follicle.…”
Section: Danger In Preovulatory Follicles For Onset Of Inim Functionmentioning
confidence: 99%
“…21 According to recent studies, ROS derived from NADPH oxidase is involved in the regulation of MCP-1 gene expression in endothelial cells. 19, 22 The aim of this study was to determine if IS induced ROS production by activating NADPH oxidase, leading to the induction of MCP-1 expression in human umbilical vein endothelial cells (HUVEC), and to clarify the mechanisms involved.…”
Section: Expression Of Mcp-1 By Indoxyl Sulfatementioning
confidence: 99%
“…As several reports have shown that ROS induces MCP-1 expression in endothelial cells, 19,22 and that NADPH oxidase is a major source of superoxide in vascular cells and monocytes, 25 we examined the effect of apocynin (600 μmol/L), a specific NADPH oxidase inhibitor, on IS-induced ROS production and MCP-1 expression. As shown in Figure 2A, HUVEC treated with IS for 2 min exhibited increased superoxide production compared with the controls, but pretreatment with apocynin for 30 min significantly reduced their ROS production, indicating that IS-induced ROS production in HUVEC was most likely derived from NADPH oxidase activity.…”
Section: Nadph Oxidase-derived Ros Mediates Is-induced Mcp-1 Expressimentioning
confidence: 99%
See 1 more Smart Citation